2009
DOI: 10.1093/nar/gkp550
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast growth factor 1 induced during myogenesis by a transcription–translation coupling mechanism

Abstract: Fibroblast growth factor 1 (FGF1) is involved in muscle development and regeneration. The FGF1 gene contains four tissue-specific promoters allowing synthesis of four transcripts with distinct leader regions. Two of these transcripts contain internal ribosome entry sites (IRESs), which are RNA elements allowing mRNA translation to occur in conditions of blockade of the classical cap-dependent mechanism. Here, we investigated the function and the regulation of FGF1 during muscle differentiation and regeneration… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
36
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 47 publications
5
36
0
Order By: Relevance
“…As shown in Figure 1B, treatment with CTX in skel- etal muscle induced regeneration on day 3, evidenced by the up-regulation of Myog at both the mRNA and protein levels. These observations confirm previous reports [24,25]. Conversely, CIBZ protein was down-regulated on days 1 and 3 post-injection, whereas CIBZ mRNA levels did not change appreciably.…”
Section: Cibz Expression Is Down-regulated During Myoblast Differentisupporting
confidence: 92%
“…As shown in Figure 1B, treatment with CTX in skel- etal muscle induced regeneration on day 3, evidenced by the up-regulation of Myog at both the mRNA and protein levels. These observations confirm previous reports [24,25]. Conversely, CIBZ protein was down-regulated on days 1 and 3 post-injection, whereas CIBZ mRNA levels did not change appreciably.…”
Section: Cibz Expression Is Down-regulated During Myoblast Differentisupporting
confidence: 92%
“…The increase expression of FGF-1 induced by 1,25D-3 agrees with the concept that FGF-1 up-regulation is required for myoblast differentiation since FGF-1 knock-down by siRNA attenuates Myogenin induction originating in abnormal myotubes [16]. Moreover, it has been shown that FGF-1 is expressed in dystrophic muscle, suggesting a positive role in the regeneration of skeletal muscle fibers [36, 37].…”
Section: Discussionsupporting
confidence: 75%
“…Fibroblast growth factor-1 (FGF-1), a member of the heparin-binding growth factor family and a well-known pro-angiogenic factor, is induced during myogenesis and is required during myoblast differentiation [16]. Vascular endothelial growth factor alpha (VEGFa) another key inducer of angiogenesis, is regulated as part of the myogenic differentiation program and regulates myogenesis in an autocrine function [17].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, IRES have been identified in several mammalian mRNAs, mainly in control genes such as transcription factors and growth factors (Vagner et al, 2001). For instance, functional IRESs have been recently identified in Fibroblast Growth Factor 1 (Martineau et al, 2004;Conte et al, 2009), which plays a crucial role in myoblast differentiation. It is noteworthy that a number of genes including the hypoxiainducible genes encoding HIF-1a remain preferentially translated when eIF4E is sequestered by its repressor 4E-BP (Wouters and Koritzinsky, 2008) and we show that HIF-1a mRNA levels increased depending on the oxygen availability.…”
Section: Discussionmentioning
confidence: 99%